The effect of scanning strategy on the thermal behavior and residual stress distribution of damping alloys during selective laser melting - Wu, Kaiwen (Nanyang Technological University, 2024)
The manufacture of damping alloy parts with stable damping properties and high mechanical performances in the selective laser melting (SLM) process is influenced by temperature evolution and residual stress distribution. Choosing an appropriate scanning strategy, namely the specific trajectory along which the laser head scans powders within given area, is crucial, but clearly defined criteria for scanning strategy design are lacking. In this study, a three-dimensional finite element model (FEM) of the SLM process for manufacturing a WE43 alloy component was established and validated against published experimental data, where WE43 is a kind of Mg-Y based alloy that has good high temperature strength and creep resistance, and thus widely used in aerospace applications. The FEM mainly includes the modelling of geometry, heat transfer (governing equation, boundary conditions, and heat source), and materials, by conducting the thermal-mechanical coupled calculation, this model could reflect the influence of difference in scanning strategy applied, under an ideal circumstance. Eleven different scanning strategies were designed and simulated, considering variables such as scanning track length, direction, Out-In or In-Out strategy, start point, and interlayer variation. Results showed that scanning strategy, geometry, and layer number collectively affect temperature, melt pool, and stress outputs. For instance, starting scanning at a colder part of the powder layer could lead to high peak temperature and low melt pool depth. Higher layer number generally results in lower cooling rate, lower temperature gradient, longer melt pool life and larger melt pool dimensions. Changing the start point between scanning circulations helps mitigate detrimental residual stress. This work highlights the potential of analyzing various scanning strategy-related variables, which contributes to reducing trial-and-error tests, and selecting optimal scanning strategies under different product quality requirements. By reading this thesis, appropriate scanning strategies can be designed to prevent defects such as element loss due to evaporation, poor bonding, and deformation or cracking from high residual stress. Additionally, identifying stress concentration locations and understanding the effects of geometry and layer number on thermal and mechanical behaviors can assist in geometry design.